2023
DOI: 10.1142/s0218625x23500051
|View full text |Cite
|
Sign up to set email alerts
|

DEPOSITING Ni–Co–P ALLOY COATING ON AISI316 STEEL AND ANALYZING ITS PROPERTIES

Abstract: After appropriately preparing the surface of AISI316 steel, the Ni–Co–P coating layer was deposited on the substrate using the electroless method using baths with different mole ratios of CoSO4/NiSO[Formula: see text]. Coating rate, weight percentage of the alloy elements, corrosion rate and coating layer hardness were studied in the achieved coating layers. The coating rate of the Ni–Co–P coating layer is a function of the mole ratio of CoSO4/CoSO[Formula: see text], sodium hypophosphite concentration, bath t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Meanwhile, Ni-P films with low phosphorus content (3-5% P) have good corrosion resistance in concentrated sodium hydroxide solution, and Ni-P alloys with medium or high phosphorus content have excellent corrosion resistance in acidic solutions and in chloride medium [5,12,13]. Typically, to improve the qualities of the electroless binary Ni-P alloy, ternary Ni alloys were created using the codeposition technology of Ni to give the ternary alloys, such as Ni -W -P [14,15], Ni -P -B [16][17][18], Ni -Fe -P [19][20][21], Ni -Cu -P [22][23][24][25], Ni -Co -P [26][27][28][29], Ni -Sn -P [30][31][32][33][34][35] and Ni For instance, studies have found that Ni -Sn -P alloys with low Sn content have good corrosion resistance. However, the majority of the work on Ni-based alloys was done at higher temperatures, such as 80-95 °C [36].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Ni-P films with low phosphorus content (3-5% P) have good corrosion resistance in concentrated sodium hydroxide solution, and Ni-P alloys with medium or high phosphorus content have excellent corrosion resistance in acidic solutions and in chloride medium [5,12,13]. Typically, to improve the qualities of the electroless binary Ni-P alloy, ternary Ni alloys were created using the codeposition technology of Ni to give the ternary alloys, such as Ni -W -P [14,15], Ni -P -B [16][17][18], Ni -Fe -P [19][20][21], Ni -Cu -P [22][23][24][25], Ni -Co -P [26][27][28][29], Ni -Sn -P [30][31][32][33][34][35] and Ni For instance, studies have found that Ni -Sn -P alloys with low Sn content have good corrosion resistance. However, the majority of the work on Ni-based alloys was done at higher temperatures, such as 80-95 °C [36].…”
Section: Introductionmentioning
confidence: 99%